2008
DOI: 10.1007/s11409-008-9033-1
|View full text |Cite
|
Sign up to set email alerts
|

The development of two observational tools for assessing metacognition and self-regulated learning in young children

Abstract: This paper reports on observational approaches developed within a UK study to the identification and assessment of metacognition and self-regulation in young children in the 3-5 year age range. It is argued that the development of observational tools, although containing methodological difficulties, allows us to make more valid assessments of children's metacognitive and self-regulatory abilities in this age group. The analysis of 582 metacognitive or self-regulatory videotaped 'events' is described, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
293
0
43

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 377 publications
(401 citation statements)
references
References 47 publications
13
293
0
43
Order By: Relevance
“…For long, research on self-regulation has prevalently focused on older students as scholars questioned whether younger students possessed the knowledge and strategies necessary for self-regulated learning (Paris & Newman, 1990;Zimmerman, 1990). Increasingly, however, researchers postulate that students in elementary school are able to regulate their learning (e.g., Perry, 1998;Whitebread et al, 2009). In a similar vein, research focuses more and more on identifying classroom conditions that foster the development of cognitive and metacognitive strategies (Ley & Young, 2001;Paris & Paris, 2001;Perry & VandeKamp, 2000).…”
mentioning
confidence: 99%
“…For long, research on self-regulation has prevalently focused on older students as scholars questioned whether younger students possessed the knowledge and strategies necessary for self-regulated learning (Paris & Newman, 1990;Zimmerman, 1990). Increasingly, however, researchers postulate that students in elementary school are able to regulate their learning (e.g., Perry, 1998;Whitebread et al, 2009). In a similar vein, research focuses more and more on identifying classroom conditions that foster the development of cognitive and metacognitive strategies (Ley & Young, 2001;Paris & Paris, 2001;Perry & VandeKamp, 2000).…”
mentioning
confidence: 99%
“…These results and approach can be considered crucial to informing self-regulation research and practice and establishing musical play's importance in this regard. 3 The CHILD achieves high levels of internal consistency amongst its 22 statements (Cronbach alpha=.97), and provides high inter-rater reliability (level of agreement= 85.9%) (Whitebread et al, 2009b) …”
Section: Resultsmentioning
confidence: 99%
“…This study reported that different areas of selfregulatory behaviours appeared at different rates, with metacognitive regulation being the most prevalent, followed by metacognitive knowledge, and emotional/motivational regulation behaviours being the least frequent (Whitebread et al 2009a). More specifically, playful situations appeared to mainly promote monitoring, control and planning behaviours (Whitebread et al, 2009b) The Social Nature of Self-regulation Notwithstanding the traditional focus on the individual element of selfregulated learning (Zimmerman, 1989), the social nature of regulation is currently an increasingly central theme (Hadwin, Oshige, Gress, & Winne, 2010;Volet, Vauras, & Salonen, 2009). Current research suggests that, apart from self-regulated learning, attention should be directed towards co- Affording for Regulation regulation and socially-shared regulation (Hadwin, Järvelä, & Miller, 2011;Iiskala, Vauras, & Lehtinen, 2004).…”
mentioning
confidence: 99%
“…It is completed by mothers. When developing the Assessing Self-Regulation Skills Scale, an item pool was created by reviewing the literature (Bodrova & Leong, 2008;Bronson, 2000;Carlson & Wang, 2007;Eisenberg, 2012;Eisenberg & et al, 2004;Whitebread & Basilio, 2011;Whitebread & et al, 2009). Then, the scale was assessed by two early childhood teachers and four field experts in terms of the items' appropriateness and clarity.…”
Section: Methodsmentioning
confidence: 99%